Linking two dimensions of entrepreneurial orientation to firm performance: the moderating effect of government's role / Melvin Mojikon, Azizan Abdullah And Sofian Shamsuddin - Mojikon, Melvin; Abdullah, Azizan; Shamsuddin, Sofian (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
Entrepreneurial Orientation (EO) has been defined as a strategic orientation method, which employed by firms to identify ways and in creating a specific set of opportunities through various decision-making skills and entrepreneurial practices. Hence, this study was conducted based on the phenomenon experienced by a number of manufacturing firms in Sabah, Malaysia, within the context of Small and Medium-Sized Enterprises (SMEs). The EO, moreover, was deemed as a multidimensional construct encompassing two dimensions, namely competitive aggressiveness and pro-activeness. The study took place in Sandakan which is situated in Sabah. Based on the attributes of EO consisting of competitive aggressiveness and pro-activeness, the results were statistically demonstrated a significant relationships with firm performance. Whereas the government, which usually plays an important role, as the moderator, portrayed an insignificant and non-influential role in strengthening the relationships between these two EO dimensions and firm performance.